Innate Immunity in Simian Immunodeficiency Virus Infection - Reeves, Roger Keith (Natural Hosts of SIV, 2014)
The past decade has seen the emergence of innate immunity as a mature field. The study of innate immunity has had a significant impact on the concepts of HIV immunity, pathogenesis, and vaccines. In this chapter, basic concepts of innate immunity at the anatomical, cellular, and molecular levels will be introduced from the perspective of their interplay with HIV and simian immunodeficiency virus (SIV). An emphasis will be placed on studies using SIV/non-human primate (NHP) models that shape current models of HIV pathogenesis. Finally, studies modulating the innate system in vivo in NHPs will be discussed.